An exploratory study of nonprofit organisations' use of the internet for communications and fundraising. (2016) - Shin, Namchul; Chen, Qian
This research examines how nonprofits use the internet to build public relations and increase charitable giving by analysing the content of the websites of various nonprofit organisations listed in the top 100 NPOs published by The Nonprofit Times. While there is no difference for most variables in the fundraising and communication practices between top tier ; and bottom tier NPOs divided by total revenue, the differences are found in such variables as campaign summary, messages from the CEO, volunteer opportunities, information sharing, social media use, and annual reports. These findings suggest that certain communication practices (information dissemination, interactive communication, and accountability) are positively associated with the level of fundraising. Compared to the findings of previous research, however, our findings show that the presence of characteristics related to communications and fundraising has increased on NPOs' websites. This indicates that by recognising the importance of the internet, NPOs are increasingly using it as a medium for communications and charitable giving.